The Role of Temporal Contingency and Integrity of Visual Inputs in the Sense of Agency: A Psychophysical Study - Mizuhara, Hiroaki; Uhlhaas, Peter (Frontiers in Psychology, 2021)
The sense of agency is a subjective feeling that one's own actions drive action outcomes. Previous studies have focused primarily on the temporal contingency between actions and sensory inputs as a possible mechanism for the sense of agency. However, the contribution of the integrity of visual inputs has not been systematically addressed. In the current study, we developed a psychophysical task to examine the role of visual inputs as well as temporal contingencies toward the sense of agency. Specifically, participants were required to track a target on a sinusoidal curve on a computer screen. Visual integrity of sensory inputs was manipulated by gradually occluding a computer cursor, and participants were asked to report the sense of agency on a nine-point Likert scale. Temporal contingency was manipulated by varying the delay between finger movements on a touchpad and cursor movements. The results showed that the sense of agency was influenced by both visual integrity and temporal contingency. These results are discussed in the context of current models that have proposed that the sense of agency emerges from the comparison of visual inputs with motor commands.